Սյունյաց Գրիգոր Բ արքայի անվանակիր սարկոֆագը - Հարությունյան, Ա. (ՀՀ ԳԱԱ հրատ.)
The sarcophagus (discovered at the wayside leading to Shaki village in 1985) exhibited at Karadaran (open-air hall of stone artfacts) of the History Museum named after Adontz in the town of Sirian. Саркофаг, обнаруженный в 1985г. на обочине дороги, ведущей в село Шаки, выставлен под открытым небом в Карадаране. (хранилище каменных артефактов при Историческом музее им. Н. Адонца в г. Сисиане.)
Keywords: Պատմություն